GALLIC ACID AND ITS SYNTHESIS OF PROPYL ETHER - Yuldasheva M.R; Kadirova Sh.O (Scholar Express Journals, 2023)
Gallic acid and its propyl ester are present as one of the major phenolic compounds in many plants, including fruits and vegetables. Gallic acid propyl ester is used as a feedstock for food, cosmetics, inks and paints, as an antioxidant in the pharmaceutical industry and for various industrial purposes. Gallic acid was treated with propyl alcohol in an acid medium to obtain gallic acid propyl ester in laboratory conditions
Keywords: gallic; rufigalic acid; iron; ester